Improving Knowledge Numbers Ability with Card Media in Early Age Children - Geraisa Dayura Chanet (International Consortium of Education and Culture Research Studies, 2020)
The initial developmental stages are the basis for further developmental stages, if a stage is interrupted, it will inhibit the next stage. Likewise in the educational process, for children aged 4 to 6 years can be formally pursued in kindergarten, and is expected to obtain physical-motor, cognitive, social, and emotional stimuli in accordance with their age level. Every child has differences, so students who cannot learn as they should are called learning difficulties. Some learning difficulties experienced by young children are reading, writing and arithmetic. Especially in learning to count, mathematics is very useful for developing thinking processes in early childhood. It also cannot be separated from the role of parents who provide physical and psychological needs at the beginning of a child's life. Therefore the purpose of this study is to find out the cause of a 5-year-old child who cannot memorize numbers 1-10. The method in this study uses a qualitative research design with a single case experience with the provision of interventions, namely the introduction of numbers with the media card and assistance and counseling to parents. The intervention was carried out at the subject's home for two weeks for six meetings. The results obtained during six meetings, subjects can recognize the symbol numbers 1-10. The subject better understands numerical symbols by looking at cards or visually. This affects the subject's learning process at school and at home. The subject can continue the process of understanding number symbols using cards or learning visually